Welcome letter from the editor - Montgomery, Philip (NUGSE Research in Education, 1(1), 2016)
Scholarly research is as much a science as it is an art. The articles presented in this inaugural issue of NUGSE Research in Education reflect the high academic and ethical standards of educational research and policy analysis. All of our authors have completed graduate or postgraduate courses in research methods and educational policy studies. They have chosen and researched the topics themselves, topics which are relevant to education in Kazakhstan and which deserve a wider audience. This critical and analytical inquiry can and will bring positive change to schools, universities and governmental organizations, by placing value on passionate intellectual curiosity and meticulous evidence-based decision-making. The very act of writing, reviewing and editing these articles, we hope, will encourage students to tackle the big problems and wrestle with the big ideas in their field.
Keywords: NUGSE Research in Education; NUGSE; scholarly research